Paradigma Tematik-Integratif dalam Pengembangan Kurikulum dan Pembelajaran PAI di Madrasah: Suatu Kajian Teoretik - Muhammad Alwi Alfarezi; Sabily Hilmah Mukaddar (Indo Publishing, 2026)
In the rapidly evolving digital era of 2025, Islamic Religious Education (PAI) in Indonesia faces significant challenges in shaping resilient Islamic character among students who spend considerable time on digital devices. This study aims to develop a PAI curriculum model based on Islamic character that integrates religious values, contextual approaches, and digital technology to address the challenges of secular and materialistic values. Employing a library research method, this study analyzes literature from curriculum development theories, Islamic character education, and digital technology utilization. The findings indicate that enhancing teacher competencies through professional training and digital literacy, innovating teaching methods such as project-based and cooperative learning, and integrating character values through intracurricular, cocurricular, extracurricular, and religious habituation pathways can improve the effectiveness of PAI learning. Challenges such as limited facilities, teacher resistance, and negative social media influences can be addressed through collaborative strategies involving parents and communities, as well as leveraging educational technology. This curriculum supports the formation of individuals with noble character, relevant to the needs of the digital era, and aligned with national education goals. The study contributes to developing PAI strategies that are responsive to social and technological dynamics.